Design of a three-phase statcom-based inductive static VAR compensator using DC capacitor voltage control scheme - Obais A.M.; Pasupuleti J. (Maxwell Science Publications, 2023)
In this study, a three-phase continuously controlled harmonic-free inductive static VAR compensator is presented. The compensator is built of a three-phase voltage source inverter based statcom. The phase currents of this compensator are linearly and continuously controlled by the statcom DC capacitor voltage. The control strategy is outlined by a process of forcing the capacitor voltage to follow a certain reference voltage which can be varied linearly from its maximum to its minimum values to produce balanced three-phase inductive currents varying in the range of zero to maximum value (IMAX). The proposed compensator was verified on the computer program PSpice. 2013 Maxwell Scientific Organization.